2012
DOI: 10.1182/blood-2011-11-393991
|View full text |Cite
|
Sign up to set email alerts
|

FGF signaling facilitates postinjury recovery of mouse hematopoietic system

Abstract: Previous studies have shown that fibroblast growth factor (FGF) signaling promotes hematopoietic stem and progenitor cell (HSPC) expansion in vitro. However, it is unknown whether FGF promotes HSPC expansion in vivo. Here we examined FGF receptor 1 (FGFR1) expression and investigated its in vivo function in HSPCs. Conditional knockout (CKO) of Fgfr1 did not affect phenotypical number of HSPCs and homeostatic hematopoiesis, but led to a reduced engraftment only in the secondary transplantation. When treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 49 publications
4
58
0
Order By: Relevance
“…The Flk1-Cre and Tie2-Cre deleter alleles used in the current study, which are known to target the hematopoietic lineage (19,48), allowed us to test the requirement for hematopoietic cell FGFR1/2 signaling during development, homeostasis, and response to injury. Consistent with Zhao et al (22), we found that inactivation of FGFR1/2 signaling in the hematopoietic lineage does not adversely affect hematopoietic development or homeostasis under normal physiological conditions. We also observed that leukocyte infiltration in DCKO and DFF mice was similar following cutaneous wounding.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The Flk1-Cre and Tie2-Cre deleter alleles used in the current study, which are known to target the hematopoietic lineage (19,48), allowed us to test the requirement for hematopoietic cell FGFR1/2 signaling during development, homeostasis, and response to injury. Consistent with Zhao et al (22), we found that inactivation of FGFR1/2 signaling in the hematopoietic lineage does not adversely affect hematopoietic development or homeostasis under normal physiological conditions. We also observed that leukocyte infiltration in DCKO and DFF mice was similar following cutaneous wounding.…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, Zhao et al (22) showed that HSPC mobilization was impaired in mice lacking FGFR1 in the hematopoietic lineage suggesting impaired migration. The Flk1-Cre and Tie2-Cre deleter alleles used in the current study, which are known to target the hematopoietic lineage (19,48), allowed us to test the requirement for hematopoietic cell FGFR1/2 signaling during development, homeostasis, and response to injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be explained by the inactive FGF signals during homeostasis with low levels of FGFs in BM and FGFRs in HSCs; however, both FGF ligands in BM and FGF receptors were boosted under stress to turn on FGF signals for promoting HSC proliferation through activation of AKT and NF-B mechanisms. Interestingly, FGF signal was also shown to play a role in mobilizing HSCs to spleen for extramedullary hematopoiesis through regulating CXCR4-CXCL12 pathway that further facilitated HSC regeneration under stress [24,58,59].…”
Section: Bone Marrow Niche Signals During Regenerationmentioning
confidence: 99%
“…Since hematopoietic stem cells (HSCs) are maintained in a quiescent state, HSCs are resistant to 5-FU induced cell death. Thus, serial 5-FU injection has been utilized to evaluate HSC cell function and maintenance in vivo [71][72][73][74] . We hypothesized that osteopetrotic mice show a reduced HSC pool and function due to lack of BM cavities and niches.…”
Section: Hematopoietic Stem Cells Are Maintained In Osteopetrotic Micementioning
confidence: 99%